Compatibility of the egg parasitoid Trichogramma minutum (Hymenoptera: Trichogrammatidae) and the granulovirus (CpGV) used in combination against the codling moth Cydia pomonella (Lepidoptera: Tortricidae) - Morisset, Olivier; Cabrera, Paula; Todorova, Silvia; Cormier, Daniel; Chouinard, Gérald; Lucas, Éric (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2021)
The codling moth granulovirus (CpGV) and the egg parasitoids of the genus Trichogramma spp. are known as biocontrol agents of codling moth but interactions between them are unknown. The aim of this study was to assess the compatibility and the complementarity of Trichogramma minutum and CpGV. Bioassays were conducted in the laboratory the first year, as well as in an orchard over two years with the two biocontrol agents used alone or in combination. Parasitism of codling moth decreased in glass tube bioassays when CpGV was applied on eggs prior to parasitism, suggesting that female parasitoids discriminated between eggs covered or not with the virus. In contrast, egg discrimination was not observed in the orchard, since the presence of CpGV on codling moth eggs did not affect T. minutum parasitism. Both biocontrol agents together caused 77 and 79% mortality to codling moth in the orchard in the first and the second year of the study, respectively. Our results in the orchard showed that the combined use of CpGV and T. minutum to control the codling moth is compatible. Therefore, the utilization of both biocontrol agents is a promising alternative to control this pest in apple orchards.